2001
DOI: 10.1002/1097-0142(20010201)91:3<561::aid-cncr1035>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Des-?-carboxy prothrombin as a useful predisposing factor for the development of portal venous invasion in patients with hepatocellular carcinoma

Abstract: BACKGROUND Portal venous invasion (PVI) in patients with hepatocellular carcinoma (HCC) is an important factor affecting prognosis. The objective of this study was to elucidate predisposing factors for the development of PVI. METHODS Two hundred twenty‐seven patients with HCC who did not show PVI and who received percutaneous ethanol injection therapy and/or microwave coagulation therapy at the time of their first hospital admission were enrolled between 1994 and 1996. After their HCC was treated, the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
211
4
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 292 publications
(236 citation statements)
references
References 39 publications
13
211
4
7
Order By: Relevance
“…The pretreatment levels of these markers are useful predictors of local tumor progression. 33,34 However, their post-treatment levels have been considered to have limited efficacy as predictors of local tumor recurrence after TACE 35 and percutaneous ablation. 36 Elevated serum levels of alpha-fetoprotein, which reflect not only tumor-cell proliferation but also active disease with continuous necrosis and regeneration, are associated with an elevated risk of developing HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The pretreatment levels of these markers are useful predictors of local tumor progression. 33,34 However, their post-treatment levels have been considered to have limited efficacy as predictors of local tumor recurrence after TACE 35 and percutaneous ablation. 36 Elevated serum levels of alpha-fetoprotein, which reflect not only tumor-cell proliferation but also active disease with continuous necrosis and regeneration, are associated with an elevated risk of developing HCC.…”
Section: Discussionmentioning
confidence: 99%
“…DCP, also known as prothrombin induced by vitamin K absence-II (PIVKA-II), is an abnormal prothrombin protein that is present at higher levels in the serum of HCC patients. Since the report by Liebman et al [18], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [86,87]. AFP-L3 is a fucosylated variant of AFP that reacts with Lens culinaris agglutinin A and can differentiate an increase of AFP due to HCC from that due to benign liver disease [20,21,82].…”
Section: Discussionmentioning
confidence: 99%
“…Levy and Sherman (2002) reported that the CLIP classification for HCC is easier to implement and more accurate than the OKUDA classification. In addition, Koike et al (2001) suggested that serum PIVKA-II level is the most useful predisposing clinical parameter for the development of portal vein invasion. To investigate the role of these clinical parameters, AFP, PIVKA-II, OKUDA score, and CLIP score were used in the present study to assess the clinical effects of IFN-a/5-FU combination therapy.…”
Section: Discussionmentioning
confidence: 99%